Low energy impact indentation of a modified polyethylene terephtalate by instrumented falling weight. Issue 4 (17th May 2012) - Martínez, A. B.; Arencón, D.; Navas, J.; Velasco, J. I.
Abstract: Investigation of the flexed plate impact of polymers requires the study of the local plate reaction during the contact between the hemispherical tip and the specimen. The current work investigates the low energy impact indentation with a hemispherical indenter applied to a polymer sheet with a ductile behavior. The samples were freely supported on a very rigid steel plate and transversely collided by the instrumented dart. The restitution coefficients are calculated, and a lumped mass‐spring model based on the Hertz law, which agrees with the experimental contact forces, restitution coefficients, indenter depth of penetration and permanent deformations is developed. This is an indirect method to estimate the Young's modulus at these relatively high strain rates. The influence of the geometrical parameters of the test such as target thickness, drop mass, indenter diameter, along with impact velocity are analyzed. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :